Development and validation of a method for the weathering and detachment of representative nanomaterials from conventional silver-containing textiles. (December 2021) - Patch, David; Koch, Iris; Peloquin, Derek; O'Carroll, Denis; Weber, Kela
Abstract: Nanotoxicology research commonly utilizes pristine nanomaterials for toxicity assessment, which may not be perfectly representative of what is released into environmental systems. The goal of the present study was to develop a method to simulate human weathering of silver-containing textiles. To achieve this goal the roles of physical and chemical stress on X-Static® containing athletic textiles were investigated and compared to data collected from human weathering experiments and literature. Chemical weathering methods (artificial sweat) were used independently and alongside physical weathering methods (3D printed stretching and abrasion instruments). Non-weathered control textiles were found to release 29 ± 11 mg Ag/kg of textile into wash water effluent (ICP-MS), with 16% being released as ionic silver (ICP-MS) and the rest as metallic nanomaterials, nanosheets, and particulates of varying size (SEM/XANES). Real and simulated human weathered textiles released similar amounts of total silver (67 ± 11 mg Ag/kg, 84 ± 13 mg Ag/kg respectively) with the silver released being composed of ionic (1.5%, 2%) and a mixture of metallic and chlorinated nanomaterials, nanosheets, and particulates. The method was shown to effectively detach environmentally representative silver materials from silver-containing textiles and can provide such materials for future studies on the assessment of their fate, transport, and toxicity. Graphical abstract: Image 1 Highlights: 3D-printed instruments successfully simulated human weathering of silver-containing textiles. Physical weathering fragmented textile coatings resulting in increased silver release. Chemical weathering chlorinated and increased the amount of silver released from textiles. Ag nanomaterial characteristics from simulated weathering matched AgNMs released by human weathering. Simulated weathering can provide relevant AgNMs for further research.